Hybrid Piezo–Electromagnetic Device Designed to Harvest the Vibrations of the Human Body - George-Claudiu Zărnescu; Lucian Pîslaru-Dănescu; Ioan Stamatin (Micromachines)
This paper focuses on hybrid piezo–electromagnetic generators, which are assembled from a magnetic repulsion pad made of two disk magnets, a sliding cylindrical magnet placed inside a tube, a coil, and an assembly of piezoelectric elements connected with the magnetic pad, as well as an electronic system for rectification and voltage adjustment. Four piezo–electromagnetic generators have been developed. Two linear generators without magnetic cores were tested and optimized for low-frequency (0.2 Hz…5 Hz) and low-amplitude body movements. The other two generators were also designed to handle high-vibration amplitudes, to generate up to 2.2–2.5 W of power. An algorithm for the calculation and modeling of these hybrid generators is presented, as well as simulation models. In addition, an electronic hybrid voltage converter was realized. It was observed that the system harvesting efficiency was increased by adding a large capacitive buffer made of electrolytic capacitors after the Schottky diode rectifiers bridges. This capacitive buffer, together with the electronic pre-regulator, has the role of limiting the voltage to the desired input value and of being the first charging stage. Finally, in the second charging stage, an electronic converter is used to charge the supercapacitors.